2020
DOI: 10.1016/j.celrep.2020.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Dorsal and Ventral Hippocampal CA3 Outputs Govern Contextual Fear Discrimination

Abstract: Considerable work emphasizes a role for hippocampal circuits in governing contextual fear discrimination. However, the intra-and extrahippocampal pathways that route contextual information to cortical and subcortical circuits to guide adaptive behavioral responses are poorly understood. Using terminal-specific optogenetic silencing in a contextual fear discrimination learning paradigm, we identify opposing roles for dorsal CA3-CA1 (dCA3-dCA1) projections and dorsal CA3-dorsolateral septum (dCA3-DLS) projection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 70 publications
4
44
1
Order By: Relevance
“…Further support for this theory comes from work looking at the role of the vHPC projection to the lateral septum (LS) in both reward and fear. A very recent study has shown that vCA3 projections to the dorsal LS suppress fear response (Besnard et al, 2020), similar to the function of vHPC projections to the LS in suppressing feeding (Sweeney and Yang, 2015). This is perhaps not too surprising as the HPC to septum projections (labeled as the Septal Hippocampus System or SHS) were central to Gray's theory of the behavioral inhibition system.…”
Section: Discussion: Overlap and Convergence In Anxiety Fear And Rementioning
confidence: 83%
See 2 more Smart Citations
“…Further support for this theory comes from work looking at the role of the vHPC projection to the lateral septum (LS) in both reward and fear. A very recent study has shown that vCA3 projections to the dorsal LS suppress fear response (Besnard et al, 2020), similar to the function of vHPC projections to the LS in suppressing feeding (Sweeney and Yang, 2015). This is perhaps not too surprising as the HPC to septum projections (labeled as the Septal Hippocampus System or SHS) were central to Gray's theory of the behavioral inhibition system.…”
Section: Discussion: Overlap and Convergence In Anxiety Fear And Rementioning
confidence: 83%
“…Thus, the vHPC role in integrating fear-associated stimuli is at least in part through its projections to the PFC and amygdala. Furthermore, how intra-vHPC signaling impacts fear and aversion related behavior is still relatively unknown and distinct roles for vDG to vCA3 to vCA1 signaling in promoting fear response are just now being discovered (Besnard et al, 2020 ; Yeates et al, 2020 ).…”
Section: Vhpc As An Arbitrator Of Conflicting Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…The dysregulation of contextual fear processing may lead to pathological fear-related disorders such as PTSD, phobias, panic disorder and depression ( Maren et al, 2013 ; Parsons and Ressler, 2013 ). The hippocampus is thought to be critical in the formation of contextual fear memory ( Bast et al, 2003 ; Besnard et al, 2020 ; Daumas et al, 2005 ; Maren, 2001 ; Maren et al, 2013 ). Hippocampal pyramidal neurons and interneurons have received much attention related to the contextual fear memory process in the mammalian brain ( Lamsa and Lau, 2019 ; Roy et al, 2017 ; Xia et al, 2017 ; Zhu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we found that optogenetic inhibition of dHPC projections to the LS during contextual 248 fear retrieval/expression disrupted fear memory performance, indicating the importance of this 249 dHPC-to-LS pathway in memory expression as well, corroborating with earlier studies (Olton et 250 al., 1978, Besnard et al, 2020. Together, our results suggest that the dHPC-to-LS pathway is 251 critical for both memory acquisition and expression.…”
Section: Dhpc-to-ls Pathway Is Critical For Memory Acquisition and Exmentioning
confidence: 67%